Economy of standards: European Association of Urology guideline changes influence treatment costs in stage I testicular cancer patients - John, Axel; Baumgart, André; Worst, Thomas; Heinzelbecker, Julia (Urologia internationalis, 2018)
Objective: The study aimed to calculate direct medical costs (DMC) during the first year of diagnosis and to evaluate the impact of guideline changes on treatment costs in clinical stage (CS) I testicular germ cell tumor (TGCT) patients in a German healthcare system. Materials and Methods: Healthcare expenditures as DMC during the first year of diagnosis for 307 TGCT patients in CS I treated at our institution from 1987 to 2013 were calculated from the statutory health insurance perspective using patient level data. Three periods were defined referring to the first European Association of Urology (EAU) guideline in 2001 as well as to subsequent major guideline changes in 2005 and 2010. Data source for cost calculations were the German Diagnosis Related Groups system for inpatient stays (version 2014) and the German system for reimbursement of outpatient care (EBM - Einheitlicher Bewertungsmaßstab, edition 2014). Results: During our 25 years of study period, mean DMC in the first year after diagnosis for the entire cohort of TGCT patients in CS I almost halved from EUR 13.000 to EUR 6.900 (p < 0.001). From 1987 to 2001, DMC for CS I seminomatous germ cell tumor (SGCT) patients were EUR 13.790 ± 4.700. From 2002 to 2010, mean costs were EUR 10.900 ± 5.990, and from 2011 to 2013, mean costs were EUR 5.190 ± 3.700. For CS I non-seminomatous germ cell tumor (NSGCT) patients, from 1987 to 2001, mean DMC were EUR 11.650 ± 5.690. From 2002 to 2010, mean costs were EUR 11.230 ± 5.990, and from 2011 to 2013, mean costs were EUR 11.170 ± 7.390. Follow-up examinations became less frequent over time, which caused a significant cost reduction for NSGCT (p = 0.042) while costs remained stable for SGCT. When adding costs of relapse treatment, active surveillance (AS) was the most cost-effective adjuvant treatment option in CS I NSGCT whereas one course carboplatin or AS caused similar expenditures in SGCT patients. Conclusion: The introduction of the EAU guidelines in 2001 caused a decrease in DMC in CS I seminoma patients. This cost reduction mainly took place due to the declining importance of radiation therapy. No substantial changes were seen in patients with CS I NSGCT. Costs for follow-up care also diminished, but to a lesser degree. Even when considering expenditures for relapse treatment, AS remained cost-effective in CS I TCGT patients. Our data show that evidence-based medicine in TGCT can reduce DMC in the first year after diagnosis.
Gesehen am 17.03.2020